Sweet syndrome with pseudocarcinomatous hyperplasia: A case report and review of the literature. (17th April 2019) - Wipf, Angela; Wipf, Heidi; Miller, Daniel
Abstract : Pseudocarcinomatous (pseudoepitheliomatous) hyperplasia represents reactive epidermal change mimicking squamous cell carcinoma (SCC), owing to a variety of inflammatory and neoplastic phenomena, including deep fungal infections, CD30‐positive lymphomas, and others. We report a case of Sweet syndrome (SS) arising in a patient with acute myelogenous leukemia, with persistent orolabial involvement which mimicked SCC both clinically and microscopically, but resolved entirely with adequate corticosteroid treatment. Clinicians should be aware that neutrophilic dermatoses such as SS and pyoderma gangrenosum may rarely exhibit pseudocarcinomatous epidermal changes similar to those seen in soft tissue infections and other inflammatory dermatoses.